Visionary Principal: Islamic Leadership to Achieve Satisfaction with Education Services - Sukatin, Sukatin; Hariyanto, Mashudi; Sawitry, Maryanti; Munawaro, Siti; Amrizal, Amrizal (Universitas Islam Negeri Raden Intan Lampung, 2022)
Elementary schools, as institutions that coordinate the educational process, should aspire to teach the nation's life in order to generate the next generation of competitive global citizens. This study aimed to identify school principal leadership that can increase educational quality by increasing service satisfaction. Madrasah Ibtidaiyah Negeri 1 Batanghari, Jambi was the site of the study and uses a descriptive qualitative approach. According to the study's findings, the leadership of a visionary school administrator is capable of realizing student and parent satisfaction with educational services, resulting in quality education.